Refleksje na temat książki Sebastiana Fikusa „Trudny spadek dysydentów III Rzeszy w Republice Federalnej Niemiec” - Zmierczak, Maria (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
The reviewed book contains a description of state policy towards the German opponents of Hitler’s regime after the fall of the Third Reich. The death sentences of military courts, Volksgericht and special war courts were treated as legal and the victims and their descendants were not vindicated until 2009. It means that they figured as criminals for more than 50 years. The author suggests that this was connected mainly with economic reasons and the need to restore the national economy. The commentary of the reviewer underlines the importance of other aspects: on the one hand, it was not easy to declare that the Federal Republic of Germany is a new state and to break the continuity of state, especially in the face of the existing German Democratic Republic. On the other hand, it is not easy to declare that the law was not legal, and to punish judges or officers who had acted according to the legal prescriptions; not to mention the old sentence lex retro non agit.
Keywords: dysydenci; przeciwnicy; Hitler, Adolf (1889-1945); Republika Federalna Niemiec; procedury prawne; rehabilitacja